Adult‐type ALCAPA syndrome: A rare coronary artery anomaly. Issue 7 (11th May 2018) - Patrianakos, Alexandros P.; Hatzidakis, Adam; Marketou, Maria; Parthenakis, Fragiskos I.
Abstract : Anomalous origin of the left coronary artery arising from the pulmonary artery (ALCAPA or Bland–White–Garland syndrome) is a rare but serious congenital coronary artery anomaly, with a poor prognosis without surgical repair. There are two types of ALCAPA syndrome: infant type and adult type. We present a rare case of a 63‐year‐old female patient, with isolated left anterior descending artery origin from the pulmonary artery. Coronary computed tomography angiography revealed giant and tortuous coronary arteries with many collaterals between the left and right coronary system. The patient refused any surgical treatment.